Relevansi Penafsiran QS. Yunus Ayat Lima Dengan Hisab Urfi Khumasi Habib Seunagan Aceh dan KH. Ismail Suger - Abdul Fakkar Alelengo; Idris Idris; Aspandi Aspandi (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2022)
This journal discusses the relevance of QS interpretation. Yunus verse five with reckoning urfi khumasi habib seunagan aceh and kh. Ismail suger. Hisab urfi is one of the divisions of the reckoning method in determining the beginning of hijriah. It's just that in this case, the discussion is more focused on the local reckoning urfi khumasi put forward by habib seunagan aceh and kh. Ismail suger. QS Relevance. Yūnus verse five with reckoning urfi khumasi habib seungan aceh and kh. Ismail suger, it lies in further review through the interpretation of the QS. Jonah verse five itself. This journal is designed using qualitative methods, namely by taking the type (Library Research) and using descriptive-analytic methods. Here, the author will try to analyze the relevance of the interpretation of the QS. Yūnus verse five with local urfi khumasi reckoning. As for the interpretations raised, there are several works of interpretation, starting from the interpretation of the classical era such as the interpretation of Al-Faŗah, the medieval era such as the interpretation of Al-rāzi, as well as the modern and contemporary era such as the interpretation of Al-Jawāhir. The results of this study, in fact, can find out the discussion related to the relevance of the interpretation of the QS. Yunus verse five with reckoning urfi khumasi habib seuanagan aceh and kh. Ismail suger. Its relevance can be known by observing every movement of the new moon, which surrounds its manzilah or its orbit (Lunar Mantion). From there, so that the reckoning of urfi habib seunagan aceh and kh. Ismail suger can be applied from astronomers or for the community, especially in determining hijriah.